Case Report: Multimodality Imaging of Infectious Sacroiliitis and Retroperitoneal Abscess Causing Hindlimb Ataxia in a Young Dog - Jeong, Jeongyun; Ko, Jaeeun; Kim, Jaehwan; Eom, Kidong; Cho, Youngkwon; Lee, Kichang; Yoon, Hakyoung (Frontiers in Veterinary Science, 2021)
A 3-month-old intact male Labrador Retriever was presented for falling trauma and hindlimb ataxia . Radiography indicated radiolucent left sacroiliac joint with irregular margin. CT revealed thickened sublumbar muscles and hypoattenuated sacroiliac joint while MRI demonstrated abscess at retroperitoneum and gluteal muscle. US showed lytic left sacroiliac joint with retroperitoneal fluid, and FNA resulted S. aureus. Hindlimb ataxia was attributed to infectious sacroiliitis and its secondary retroperitoneal abscess. As far as the authors’ knowledge, this is the first report of multimodality imaging of infectious sacroiliitis with retroperitoneal abscess caused by S. aureus in a dog.